Pengaruh Pengendalian Internal, Investasi Aktiva Tetap, dan Beban Pajak Tangguhan Terhadap Indikasi Penghindaran Pajak dengan Komite Audit sebagai Pemoderasi - Fahreza, Rizki Aria; Kurnia, Kurnia (Universitas Batanghari Jambi, 2024)
Audit committee size is used as a moderating variable in this study to see how deferred tax expense affects indications of tax avoidance after being moderated and to see the effect of internal control, investment in fixed assets, and deferred tax expense affecting indications of tax avoidance before being moderated. Tax is a mandatory contribution that must be given to the state. This study used 100 observational samples from 20 energy sector companies listed on the Indonesia Stock Exchange between 2017 and 2021. Panel data regression analysis and moderation regression were used as analytical methods in this study. The findings show that the indicator of tax avoidance is simultaneously influenced by internal control variables, fixed asset investment, and deferred tax expenses. The fixed asset investment variable has a negative impact on indications of tax avoidance. However, indications of tax avoidance are not affected by internal control variables and deferred tax expense. In addition, deferred tax expense for indications of tax avoidance is not affected by the size of the audit committee.